Listerine – for the bridesmaid who's never a bride: Disparaging humour increases brand attitude and recall among the powerless. Issue 7 (11th July 2016) - Newton, Joshua D.; Wong, Jimmy; Newton, Fiona Joy
Abstract : Purpose: While the potential benefits of integrating humour into advertisements are widely understood, the reasons why these effects emerge are not. Drawing on literature about the impact of psychological feelings of power, this research aims to examine how power motivation interacts with the presence of disparaging humour in ads to influence ad-related outcomes. Design/methodology/approach: Following the measurement (Study 1) or manipulation (Study 2) of power motivation, participants viewed an ad featuring either disparaging humour or one of the following alternatives: no humour (Study 1) or non-disparaging humour (Study 2). Sense of superiority, brand attitude, ad claim recall and the perceived humorousness of the ad were then assessed. Findings: Featuring disparaging humour in an ad increased participants' sense of superiority, but only among those with high power motivation. Among such participants, this heightened sense of superiority increased the perceived humorousness of the disparaging humour (Studies 1 and 2), induced more favourable attitudes towards the brand featured in the ad (Studies 1 and 2) and enhanced ad claim recall (Study 2). These effects did not, however, extend to ads featuring non-disparaging humour (Study 2), indicating that it was the presence of disparaging humour, and not humour per se, that was responsible for these effects. Originality/value: These findings break open the "black box" of humour by identifying why consumers perceive disparaging humorous content to be funny, when this effect will occur and what impact this will have on advertising-related outcomes.